2016
DOI: 10.1002/2015jf003601
|View full text |Cite
|
Sign up to set email alerts
|

Meltwater influences on deep stick‐slip icequakes near the base of the Greenland Ice Sheet

Abstract: We detected over 11,000 stick-slip icequakes near the base of the western margin of the Greenland Ice Sheet using a 17-seismometer array. These icequakes have negative (i.e., very small) moment magnitudes and, according to similarities in their waveforms, group into over 100 distinct clusters distributed beneath our 3 × 3 km study area. Some clusters were active for several weeks, while others have burst-like episodes lasting 1-6 days only. Some clusters correlate with subglacial water pressure measured within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 103 publications
(174 reference statements)
5
46
0
Order By: Relevance
“…The low hydraulic connectivity that differentiates these regions from the rest of the distributed system may be due to local bed geometry causing smaller cavity orifices or the presence of low hydraulic conductivity till. Indeed, extensive subglacial till has been identified at FOXX21, and stick-slip ice motion observed seismically is associated with spatially differing connectivity of till23. More generally, both modelling4849 and observations2150 have argued for the existence of significant amounts of till underlying marginal regions of the GrIS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low hydraulic connectivity that differentiates these regions from the rest of the distributed system may be due to local bed geometry causing smaller cavity orifices or the presence of low hydraulic conductivity till. Indeed, extensive subglacial till has been identified at FOXX21, and stick-slip ice motion observed seismically is associated with spatially differing connectivity of till23. More generally, both modelling4849 and observations2150 have argued for the existence of significant amounts of till underlying marginal regions of the GrIS.…”
Section: Resultsmentioning
confidence: 99%
“…recently described direct observational evidence that even where channelization occurs, it is unable to explain lowering ice speed during late summer. At the extensively studied drill site FOXX in western Greenland41420212223 (Fig. 2a), water pressure in moulins feeding subglacial channels showed little change during the latter part of the melt season, yet velocities were observed to decrease over this same time period (Fig.…”
mentioning
confidence: 99%
“…Roeoesli et al [] recently reported the first seismogenic stick‐slip events beneath the Greenland Ice Sheet. The seismic monitoring network was located on a relatively slow‐flowing (0.27 m d −1 ) part of the ice sheet.…”
Section: Seismic Source Processesmentioning
confidence: 99%
“…There have been a few efforts focused on the impact of infiltrated surface meltwater on ice stream dynamics. Roeoesli et al () found a short‐term increase in surface velocity correlated with an increase in subglacial water pressure. Additionally, Joughin et al () documented a short‐duration surge in Ryder Glacier over a 7 week period due to drainage of a large supraglacial lake during the 1995 melt season.…”
Section: Introductionmentioning
confidence: 99%